THE EFFECT OF BOARD DIVERSITY, SUSTAINABILITY RISK RATING, ENVIRONMENTAL PERFORMANCE, AND MEDIA EXPOSURE ON ESG DISCLOSURE - Melida, Sukma; Surifah, Surifah (Universitas Tidar, 2024)
The impact of environmental performance, media attention, board diversity, and sustainability risk rating on the ESG disclosure of Kompas100 businesses listed on the BEI in 2021–2023 is investigated in this study. The ESG disclosure is the dependent variable. Media exposure, environmental performance, sustainability risk rating, and board diversity are examples of independent variables. The company's website has sustainability and annual reports, which provide secondary data for this study. Purposive sampling with preset criteria was the method employed, yielding a sample of 79 businesses with 175 data points. Multiple linear regression using SPSS is the data analysis method. The study's findings show that while environmental performance has little bearing on ESG disclosure, board diversity, sustainability risk rating, and media exposure all have a favorable impact.